Optimization of Actuators in Smart Truss Based on Genetic Algorithms - Jingjun Zhang; Minghui Luo; Ruizhen Gao; Lili He (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Actuators formed from piezoelectric ceramics were embedded in truss rods to make up active rods. The paper used mechanical knowledge, static stiffness method and the finite element method to analyze the active rod and the smart truss structure and then model them. In order to solve the difficult problem of number optimization, the paper put forward the actuator existence variable and optimized number and locations of actuators at the same time, made the structure have the best output effect, so it can reduce the displacement at the designated location of the truss structure and the structure vibration. It also can improve the truss structure accuracy. Then find the optimal solution by genetic algorithms（GA） and MATLAB programming. The results of the example show that the model this paper builds is correct and genetic algorithms are effective in solving the optimization question. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1552